Human rights as governmentality - Nasir, Muhammad Ali (2019)
This inquiry analyzes human rights as a systemic phenomenon. One of the central arguments of this inquiry is that it is not possible to consider human rights claims in abstraction from the question of institutional structures, processes of subjectification, the provision of collective goods, and the normative ideas concerning what it means to be a human. The empirical focus of the discussion is European human rights law.
Gesehen am 08.11.2019
Keywords: Hochschulschrift; Gouvernementalität; Menschenrecht